Digital Leadership and Job Satisfaction: The Role of Intrinsic Motivation as Mediating Variable - Ayun, Tiara Qurata; Erlin, Nia Ariyani (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
In order to have a flexible, effective workplace that promotes the psychological health of employees, leaders must be able to use technology into their leadership style. The purpose of this study is to examine how digital leadership affects PT Semen Padang employees' job satisfaction using intrinsic motivation as a mediating factor. 140 respondents were chosen using proportionate random sampling approaches for this quantitative study, which use the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique. The study's findings suggest that intrinsic motivation and job satisfaction are positively and significantly impacted by digital leadership. The association between digital leadership and job satisfaction has been shown to be considerably mediated by intrinsic motivation, which likewise has a positive and considerable impact on job satisfaction. The Self-Determination Theory (SDT), which holds that meeting fundamental psychological needs like competence, autonomy, and connectivity can boost intrinsic motivation and eventually lead to greater job satisfaction, is supported by these findings. The study's results highlight how crucial it is for managers to cultivate digital leadership as a tactic for raising worker motivation and job satisfaction, particularly when dealing with the difficulties posed by digital transformation in the industrial workplace.